2021
DOI: 10.1007/s00367-020-00683-3
|View full text |Cite
|
Sign up to set email alerts
|

Seismic stratigraphy of the Klints Bank east of Gotland (Baltic Sea): a giant drumlin sealing thermogenic hydrocarbons

Abstract: This work analyses six high-resolution multi-channel seismic profiles across the Klints Bank east of Gotland. The Klints Bank consists of a drop-shaped increase of the Quaternary thickness and is oriented in an approximately north-southern direction with a length of over 50 km, a width of about 15 km and a maximum thickness of 150 m. The glacial origin of the Klints Bank can be verified with the dataset presented in this study. We classify the feature as a (giant) drumlin due to its steep up-ice and tapered do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 51 publications
(71 reference statements)
4
11
0
Order By: Relevance
“…In the sub-bottom profiler data (Figures 5 and 6b) we do not observe any typical signs for those layers or shallow biogenic hydrocarbons, such as increased seismic blanking or reverberations. Similar migration paths were also proposed by Sivhed et al (2004) and Schäfer et al (2021). The migration from the Cambrian and Ordovician source rocks toward the Silurian and Devonian layers-where we observe the hydrocarbons -can be facilitated through for example, small-scale fractures such as those observed within the Silurian strata in Figures 4a and 4c.…”
Section: Fluid Origin and Migration Pathssupporting
confidence: 85%
See 3 more Smart Citations
“…In the sub-bottom profiler data (Figures 5 and 6b) we do not observe any typical signs for those layers or shallow biogenic hydrocarbons, such as increased seismic blanking or reverberations. Similar migration paths were also proposed by Sivhed et al (2004) and Schäfer et al (2021). The migration from the Cambrian and Ordovician source rocks toward the Silurian and Devonian layers-where we observe the hydrocarbons -can be facilitated through for example, small-scale fractures such as those observed within the Silurian strata in Figures 4a and 4c.…”
Section: Fluid Origin and Migration Pathssupporting
confidence: 85%
“…A similar assumption was made by Schäfer et al. (2021), who observed hydrocarbon accumulations underneath the Quaternary units of the Klints Bank. They suggested that these accumulations must have migrated there and based on the tectonic setting also assumed an updip migration from the southeast toward the northwest.…”
Section: The Baltic Basinsupporting
confidence: 80%
See 2 more Smart Citations
“…Further north and east of Gotland Basin, Schäfer et al (2021) interpreted phase reversed seismic reflections beneath the Quaternary Klints Bank drumlin as evidence for hydrocarbon gas accumulation of thermogenic origin.…”
Section: Petroleum System and Shallow Gas Expressionsmentioning
confidence: 99%